Shear behavior of transverse UHPC wet joint in prefabricated bridge deck with confining stress - Jinlong Jiang; Zhengsheng He; Hongjie Wang; Zhongya Zhang; Yanjiang Yu; Yang Zou (Case Studies in Construction Materials, 2025)
Ultra-high performance concrete (UHPC) can be applied to the transverse joints of prefabricated steel-concrete composite beams, leveraging its excellent mechanical properties to enhance the continuity and integrity of prefabricated bridge decks. A new type of UHPC wet joint with a narrow width is proposed, which can simplify the joint structure and improve the connection efficiency of adjacent prefabricated bridge decks. Shear tests were conducted on six UHPC wet joints and two epoxy dry joints to investigate the effects of joint type, reinforcement arrangement, and confining stress on shear properties. The results show UHPC wet joint can also achieve reliable connection to adjacent prefabricated bridge decks compared with epoxy dry joint, but its good ductility increases the ultimate load of prefabricated bridge deck by more than 53.0 %. When confining stress is 1 MPa or double-row reinforcements are arranged in the joint, the shear failure of prefabricated bridge deck rather than bonding interface occurs. The reinforcements of UHPC wet joint need to be arranged in double rows under no confining stress when top width is 40 mm and bottom width is 60 mm. Shear capacity is reduced by 15.7 %, and vertical dislocation is increased by more than 3.9 times when the defect area of the bonding interface at the joint is 30 %. The anchorage length of embedded reinforcement in UHPC wet joint is 4 cm. Two shear capacity formulas of UHPC wet joints in prefabricated bridge decks under confining stress were established, and the deviation between predicted results and test results was less than 3.8 %.